PENGARUH INDEPENDENSI AKUNTAN PUBLIK, SPESIALISASI AUDITOR DI BIDANG INDUSTRI KLIEN, DAN KARAKTERISTIK PERSONAL TERHADAP KUALITAS AUDIT SERTA IMPLIKASINYA TERHADAP TINGKAT KEPERCAYAAN AUDITEE (SURVEY PADA AKUNTAN PUBLIK YANG TERDAFTAR DI BAPEPAM-LK) - R. Wedi Rusmwan Kusumah (Indonesian Journal of Economics and Business, 2012)
The subjects of this research were 82 auditors who works in 41 Public Accountant Firms in Indonesia. The research used primary data collected from questionnaires. Respondents were split into two categories, those were the public account group which consisted of the partners and the emittent group which consisted of accounting and finance managers or internal auditors. The research used the explanatory method and the hypothesis test used Structural Equation Modeling (SEM) Partial Least Square (PLS).The results of the study were as follows: (1) there is a correlation between Public Accountant Independence, Auditor’s Industry Specialization, and Personal Characteristics; (2) Public Accountant Independence, Auditor’s industry Specialization, and Personal Characteristics influence the Audit Quality both simultaneously and partially; and (3) Public Accountant Independence, Auditor’s industry Specialization, Personal Characteristics, and Audit Quality influence the Auditee’s Trust level both simultaneously and partially.The result of this research showed that the decline of auditee's trust level on the service rendered by Public Accountant caused by the decreasing audit quality of the Public Accountant. The decreasing audit quality of the Public Accountant caused by Public Accountant which-in spite of having a good specialization in client industry, but have bad personal characteristics. Therefore, the Public Accountant became unindependent in carrying out the service, and, in the end, it lead to the decline of auditee's trust level.The research showed that the public accountant independency, auditor's specialization in client industry, personal characteristics, and audit quality of the Big Four were better than non-Big Four Public Accountant Firm. This also proved that the non-Big Four Public Accountant Firm did more violation than the Big Four in Indonesia.